Deskripsi Kemampuan Awal Literasi Sains Siswa Kelas XI IPA MAN Buleleng Pada Topik Kimia Hijau - Nikmatur Rohmaya; A.A.Istri Agung Rai Sudiatmika; I Wayan Subagia (Chemistry Education Study Program Sriwijaya University, 2022)
The research aimed to 1) describe the quality of students' scientific literacy questions on the topic of green chemistry and 2) describe the students' initial scientific literacy skills in the class XI IPA1 of MAN Buleleng on the topic of Green Chemistry. The research sample consisted of students in class XI IPA of MAN Buleleng in the Academic Year 2021/2022, who had received Chemistry, Physics, and Biology content concerning Green Chemistry. The research instruments were scientific literacy test questions in 30 multiple choices compiled on Google Form. The research data analysis technique used the quantitative descriptive analysis method. Based on the results and discussions described, it can be concluded that: (1) the results of item analysis using IMB SPSS Statistic 25 reported information that all scientific literacy questions on the topic of green chemistry were valid and had very high reliability. The results of the analysis of students' literacy scores obtained information that students' initial scientific literacy skills on the dimensions of using scientific knowledge were 40% in the very low category; the dimensions for identifying questions were 50% in the low category; the dimensions for drawing conclusions based on evidence were 40% in the very low category; the dimension of understanding nature and its changes was 40% in the very low category, and the dimension of making decisions about nature and its changes was 44% in the low category. Furthermore, hopefully, the research results can be used to reference further research.Keywords: assessment; scientific literacy; green chemistryAbstrakPenelitian ini bertujuan untuk 1) mendeskripsikan kualitas soal literasi sains siswa pada topik kimia hijau, 2) mendeskripsikan kemampuan awal literasi sains siswa Kelas XI IPA 1 MAN Buleleng pada topik kimia hijau. Sampel dalam penelitian adalah siswa kelas XI IPA MAN Buleleng Tahun Ajaran 2021/2022 yang telah mendapatkan materi Kimia, Fisika dan Biologi dalam kaitannya dengan Kimia Hijau. Instrumen dalam penilian ini adalah soal tes literasi sains berupa pilihan ganda yang berjumlah 30 butir soal yang disusun pada Google Form. Teknik analisis data penelitian menggunakan metode analisis dekriptif kuantitatif. Berdasarkan hasil dan pembahasan yang telah di paparkan maka dapat disimpulkan: (1) Berdasarkan hasil analisis butir soal menggunakan IMB SPSS Statistic 25 didapatkan informasi bahwa semua butir soal literasi sains pada topik kimia hijau valid dan reliabilitas sangat tinggi. Hasil analisis skor kemampuan literasi siswa didapatkan informasi bahwa kemampuan awal literasi sains siswa pada dimensi menggunakan pengetahuan ilmiah sebesar 40% dengan kategori sangat rendah, dimensi mengidentifikasi pertanyaan sebesar 50% dengan kategori rendah, dimensi menarik kesimpulan berdasarkan bukti-bukti sebesar 40% dengan kategori sangat rendah, dimensi memahami alam dan perubahannya sebesar 40% dengan kategori sangat rendah, dan dimensi membuat keputusan tentang alam dan perubahannya sebesar 44% dengan kategori rendah. Hasil penelitian ini dapat dijadikan sebagai acuan untuk penelitian selanjutnya.Kata kunci: asesmen, literasi sains, kimia hijau